Infestasi ektoparasit pada ikan Lele Dumbo (Clarias gariepinus) di Kelurahan Kuala Pembuang Dua. - Sri Wahyuni Hastuti; Sri Herlina (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
The purpose of this research is to find out whether there is infestation in African catfish (Clarias gariepinus) and what types of ectoparasites infecting the catfish as well as the level of attack of ectoparasites against catfish in Kuala Pembuang Dua village. The research was carried in March 2020. The method in taking / examining samples is the Scraping Method which is mucus scraping from fish skin and the Biopsy Method which is taking a portion of gill tissue. The research variable is to calculate the prevalence value and intensity value of the number of fish infected with parasites. There are 3 types of parasites found in African Catfish in Kuala Pembuang Dua Village, namely Oodinium sp., Dactylogyrus sp. and Chilodonella sp. The types of parasites were found to infest parts of organs namely gills (Oodinium sp., Dactylogyrus sp. and Chilodonella sp.), Fins (Oodinium sp., and Chilodonella sp.) and mucus / mucus (Oodinium sp., and Chilodonella sp.), Fins (Oodinium sp., and Chilodonella sp.) and mucus / mucus (Oodinium sp., and Chilodonella sp.). Pevalensi value in pool I and pool II are the same, namely the highest (100%) included in the category of always (very severe infection) with the type of parasite Oodinium sp. The highest intensity value in the pool I and pool II the highest number is the same type of parasite Oodinium sp. Pool I (10,3ind / head) and pool II (16.5 ind / head) Keywords : Infestation, ectoparasites, Clarias gariepinus.